THE SOCIOLOGY OF LAW PERSPECTIVE ON CHILD PROTECTION AT THE SYAR’IYAH COURT IN ACEH - Kasim, Fajri M; Nurdin, Abidin; Ridhwan, Ridhwan (Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to examine child protection at the Syar'iyah Court in Aceh from the perspective of the sociology of law. This research uses the study of legal sociology, which is an approach that views law as a tool to create order and order in society. The approach used is a case study of child protection in court decisions in Banda Aceh, Bireuen, and Lhokseumawe regarding child guardianship. Meanwhile, data collection techniques are literature studies and court decisions. This study concluded that the Syar'iyah Court in Banda Aceh granted guardianship rights to adult male siblings and to become guardians and take care of parental inheritance. In Bireuen, guardianship rights are given to the mother for a child because her father who has a pension salary is left behind. Whereas in Lhokseumawe, guardianship rights are also given to the mother while the living father is obliged to give one million per month and education and health costs. In addition, judges also become al-Qur’an, Hadith, and the opinions of the ulama as arguments in their decisions that are in accordance with the sociological characteristics of religion in Aceh. This shows that the Syar'iyah Court as part of the social system and judges as social actors have functioned to provide child protection so as to create order and order in society.